Predicting Changes of the Cultivation Areas for Astamaran and Berhi Cultivars in Iran in the 21st Century - Maryam Afzali; javad khoshhal dastjerdi; Aziz Torahi (تحقیقات کاربردی علوم جغرافیایی)
Dates are one of the most important agricultural products exported from Iran. This plant is sensitive to environmental conditions and is not able to live and reproduce in all hot and dry areas in terms of quantity and quality. Dates have different varieties; each of them has the potential to adapt to a region of arid regions and can have the most production and economic yield in its proper place. Global warming in the last century has led planners to design pre-awareness programs and algorithms due to future climatic conditions in order to choose long-lived durable plants that can survive in future environmental conditions and have good economic yield. One of the best is the Maximum Entropy model. The aim of the present study is to identify the growth potentials of dates palm verities using CCSM4 model and scenarios of 2.6, 4.5, 0.6 and 8.5. The phonological data of cultivars were harvested by field method in 2016 and 2017. According to the model,  The results showed that the dates of Astamaran and Berhi dates are different in terms of the length of phonological growth and thermal needs until the fruit ripened, and the places prone to their growth during the 2050 and 2070 periods were not the same based on the model. In addition, to bioclimatic variables for the long-term use of long-lived perennial crops, the location data required for cultivation should be used to introduce different cultivars to the environment.